Bridging the Chasm: Addressing the Digital Divide for Equitable AI Healthcare Technologies - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The advent of Artificial Intelligence AI in healthcare promises a transformative future, offering unprecedented capabilities in early diagnosis, personalized...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics